Analysis of the Impact of Transformational Leadership on Human Capital Performance in the Real Estate Industry - Dirgayasa, I Made (International Journal of Social Service and Research, 2024)
The property industry is one of the significant sectors in the Indonesian economy. This industry plays a role in the provision of residence, place of business, and investment. In an era of increasingly fierce competition, the real estate industry needs to innovate and increase productivity. The purpose of this study is to analyze the impact of transformational leadership style on human capital performance in the real estate industry. This study used quantitative research methods. Data collection techniques in this study are by distributing questionnaires and literature studies. The data collected in this study was then analyzed through the SPSS application. The results of the study indicate that transformational leadership style has a positive and significant effect on human capital performance in the real estate industry. This indicates that the greater the use of transformational leadership styles by real estate leaders, the higher the performance of human capital. Real estate leaders need to implement a transformational leadership style to encourage employees to work harder, creatively, and productively.